Skills and knowledge competency of technical and vocational education and training graduate - Che Rus Ridzwan, Hanapi Zaliza, Mohamed Suriani, Hussain Mohd Azlan, Shahrudin Shafeeqa, Malik S., (Canadian Center of Science and Education, 2017)
Skills and knowledge competency of technical and vocational education and training graduate by Che Rus Ridzwan, Hanapi Zaliza, Mohamed Suriani, Hussain Mohd Azlan, Shahrudin Shafeeqa, Malik S.,